The Relationship of Community Knowledge and Attitudes with the Handling of Tornado Natural Disasters in Sumbul District, Dairi Regency - Rugun Togianur (Institute of Computer Science (IOCS), 2022)
Potential disasters in the territory of the unitary state of Indonesia can be grouped into 3 (three) types of disasters, namely natural disasters, non-natural disasters, and social disasters. Tornado is one of the extreme conditions that occur in the atmosphere characterized by very fast air movement and forming a vortex of air column. Based on the description, the data above and the incident above, so that researchers are interested in researching the relationship between the title of knowledge and attitudes of the community with the handling of the tornado natural disaster in Sumbul sub-district, Dairi district. The research design uses an analytical survey (explanatory research) which tries to explore how and why this phenomenon occurs. then analyze the dynamics of the correlation between phenomena, both between risk factors (independent) and effect factors (dependent). Population is the entire object of research or researched and meet the specified characteristics. The population in this study is the north, east, south and west by using the simple random sampling method (simple random sample) as many as 50 people. The cross tabulation of the results obtained between the community and the handling of the natural disaster of a tornado with a result of 0.010 and the attitude of the community with the handling of the natural disaster of a tornado in Sumbul sub-district, Dairi district, obtained a significant value with a p-value of 0.015.